A PRELIMINARY STUDY OF TEACHING READING COMPREHENSION IN SPECIAL EDUCATION CLASS - Zainudin, N.F.; Ashari, Z.M.; Kosnin, A. Mohd; Saleh, Sofiazianti; Miskam, Nuraqilah Nadjwa (International Journal of Psychosocial Rehabilitation, 2020)
There are five pillars in reading which are phonemic awareness, phonics, fluency, vocabulary and comprehension. Reading comprehension can be defined as understanding the meaning from reading outcome and it consists of narrative comprehension and expository comprehension. Although comprehension is important in reading, it was less emphasized in the special education class. Therefore, the researcher decided to investigate teacher perception of teaching reading comprehension in special education class. This study was conducted on 56 special education teachers by distributing a questionnaire to the schools that have special education integrated program. The survey consists of two sections which were demographic section and content section comprised of closed-ended and open-ended questions. This study found that the teachers faced difficulties in teaching reading comprehension in class and they need assistance to teach the comprehension to the special education student. The limitation of this study was that the items in the survey were limited to special education only hence the result cannot be generalized. Furthermore, the number of items in the survey is inadequate to discover the overall perceptions of special education teachers on teaching reading comprehension. The findings in this study provided an insight for future researcher in developing assistance or teaching aid for special education teachers on teaching reading comprehension in class.